Parásitos gastrointestinales en tres especies de Telmatobius (Anura: Telmatobiidae) de la zona alto andina, Perú - Chero, Jhon; Cruces, Celso; Iannacone, Jose; Sáez, Gloria; Alvariño, Lorena; Silva, Reinaldo José da [UNESP]; Morales, Victor (My University, 2014)
During a parasitological study of semiaquatic amphibians from the high Andean region of Peru, 83 specimens of the genus Telmatobius [T. jelskii (n = 56), T. marmoratus (n = 17) and T. peruvianus (n = 10)] were purchased from markets in Lima, Peru where it is consumed liquefied Andean frogs purposes of traditional medicine, during the months of April 2009 to September 2013. According to their conservation status IUCN, T. peruvianus and T. marmoratus are vulnerable species (VU), while T. jelskii is near Threatened (NT). The parasitological analysis included total necropsy of each amphibian and search, collection, identification and standardization of its helminth fauna. The nematodes dominated in species richness and percentage of collected individuals (n = 6; 93.19%), followed by trematodes (n = 2; 4.94%), cestodes (n = 2, 1.46%) and finally, Acantocephala (n = 2; 0.42%). The three most important helminths found in Telmatobius were Hedruris moniezi, Aplectana hylambatis and Gorgoderina parvicava fluke. The parasite prevalence and abundance of all species of Telmatobius showed no association with the length of the host. Sex ratio of T. jelskii and prevalence of G. parvicava, H. moniezi, and H. moniezi were noted. Haematoloechus pukinensis, Ophiotaenia sp., H. moniezi, Cosmocercidae gen. sp., Falcaustra mascula, Aplectana vellardi, Oncicola sp. and Centrorhynchus sp. are new host records for T. jelskii. Ophiotaenia sp. is a new geographical record to the Peruvian helminthological fauna. Oncicola is reported for the first time in amphibians from Peru. Centrorhynchus sp. is reported for the second time in Peru. T. peruvianus represents a new host record for A. hylambatis and F. mascula.

Durante un estudio parasitológico de anfibios semiacuáticos de la zona alto andina del Perú, 83 especímenes del género Telmatobius[T. jelskii (n= 56), T. marmoratus (n=17) y T. peruvianus (n=10)] fueron adquiridos de mercados de la ciudad de Lima, Perú donde se consume licuado de las ranas andinas con propósitos de medicina tradicional, durante los meses de abril del 2009 a septiembre del 2013. Según su estado de conservación de la UICN, T. peruvianus y T. marmoratus se encuentran en estado vulnerable (VU), mientras que T. jelskii se encuentra casi amenazada (NT). El análisis parasitológico incluyó la necropsia total de cada anfibio y búsqueda, colección, identificación y conteo estandarizado de su helmintofauna. Los nematodos dominaron en riqueza de especies y en porcentaje de individuos colectados (n = 6; 93,19%), seguido de los trematodos (n = 2; 4,94%), cestodos (n = 2, 1,46%) y finalmente los acantocéfalos (n = 2; 0,42%). Los tres helmintos con mayor importancia especifica en Telmatobius fueron los nematodos Hedruris moniezi y Aplectana hylambatis, y el trematodo Gorgoderina parvicava. La prevalencia y abundancia de parásitos del total y de las tres especies de Telmatobius no mostró asociación con la longitud del hospedero. Se observó relación entre el sexo de T. jelskii con la prevalencia de G. parvicava y de H. moniezi, y con la abundancia de H. moniezi. Haematoloechus pukinensis, Ophiotaenia sp., H. moniezi, Cosmocercidae gen. sp., Falcaustra mascula, Aplectana vellardi, Oncicola sp. y Centrorhynchus sp. son nuevos registros para T. jelskii. Ophiotaenia sp. es una nueva adición a la fauna helmintológica peruana. Oncicola es el primer registro parasitando anfibios en el Perú. Centrorhynchus sp. es el segundo registro en el Perú. T. peruvianus es un nuevo hospedero para A. hylambatis y F. mascula.
Gastrointestinal parasites in three species of Telmatobius (Anura Telmatobiidae) in the high Andes Peru
Keywords: Anura; Aplectana; Gorgoderina; Haematoloechus; Hedruris; Helminths; Anura; Aplectana; Gorgoderina; Haematoloechus; Hedruris; Helmintos